Impacts of SiO2 and MgO nanoparticles on mass transfer performance of batch liquid-liquid extraction. Issue 5 (4th May 2017) - Sepehri Sadeghian, Mohammad Sadjad; Abooali, Danial; Rahbar-Kelishami, Ahmad
ABSTRACT: Due to substantial impacts of nanoparticles on mass and heat transfer, having knowledge about different types of nanoparticles can contribute to access high efficiencies. As an investigation, in the present study, a number of liquid-liquid extraction experiments were designed by the use of Taguchi design model in order to study the impacts of SiO2 and MgO nanoparticles on mass transfer, in the batch systems. Acetic acid was considered as solute in some organic phases (i.e., n-butanol, n-butyl acetate, toluene, and chloroform), and pure water was applied as solvent. Taguchi experiment design method made more precision and convenience in the work. Final results showed reduction of mass transfer yield due to the presence of two nanoparticles used in this work.